IQ-Switch is a QF-based innocuous, silencing-free, and inducible gene switch system in zebrafish - Hong, Jeongkwan; Lee, Jae-Geun; Sohn, Kyung-Cheol; Lee, Kayoung; Lee, Seoee; Lee, Jinyoung; Hong, Jihye; Choi, Dongju; Hong, Yeseul; Jin, Hyo Sun; Choi, Dae-Kyoung; Lee, Su Ui; et al. (Nature Publishing Group, 2021)
Hong et al. describe a new transgene expression system, IQ-Switch, and its variants and characterize their applications in cell culture and zebrafish systems. They show that IQ-Switch system has several advantages over the previous inducible transgene expression switches, including the low toxicity, tunability of expression levels and low levels of gene silencing. Though various transgene expression switches have been adopted in a wide variety of organisms for basic and biomedical research, intrinsic obstacles of those existing systems, including toxicity and silencing, have been limiting their use in vertebrate transgenesis. Here we demonstrate a novel QF-based binary transgene switch (IQ-Switch) that is relatively free of driver toxicity and transgene silencing, and exhibits potent and highly tunable transgene activation by the chemical inducer tebufenozide, a non-toxic lipophilic molecule to developing zebrafish with negligible background. The interchangeable IQ-Switch makes it possible to elicit ubiquitous and tissue specific transgene expression in a spatiotemporal manner. We generated a RASopathy disease model using IQ-Switch and demonstrated that the RASopathy symptoms were ameliorated by the specific BRAF((V600E)) inhibitor vemurafenib, validating the therapeutic use of the gene switch. The orthogonal IQ-Switch provides a state-of-the-art platform for flexible regulation of transgene expression in zebrafish, potentially applicable in cell-based systems and other model organisms.